2012
DOI: 10.1152/jn.00650.2011
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal tract neurons receptive to different forelimb joints act differently during locomotion

Abstract: During locomotion, motor cortical neurons projecting to the pyramidal tract (PTNs) discharge in close relation to strides. How their discharges vary based on the part of the body they influence is not well understood. We addressed this question with regard to joints of the forelimb in the cat. During simple and ladder locomotion, we compared the activity of four groups of PTNs with somatosensory receptive fields involving different forelimb joints: 1) 45 PTNs receptive to movements of shoulder, 2) 30 PTNs rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 72 publications
(78 reference statements)
6
23
1
Order By: Relevance
“…10C). A similar finding was also reported in our other recent studies (Armer et al 2013;Stout and Beloozerova 2012). In addition, we have previously found that, among all forelimbrelated neurons, fast-conducting PTNs as a group have the highest preference to discharge during the swing phase (Stout and Beloozerova 2013).…”
Section: Activity Of Motor Cortex Neurons During Wide-stance Walkingsupporting
confidence: 91%
“…10C). A similar finding was also reported in our other recent studies (Armer et al 2013;Stout and Beloozerova 2012). In addition, we have previously found that, among all forelimbrelated neurons, fast-conducting PTNs as a group have the highest preference to discharge during the swing phase (Stout and Beloozerova 2013).…”
Section: Activity Of Motor Cortex Neurons During Wide-stance Walkingsupporting
confidence: 91%
“…PTN does not respond (arrowhead 3) because in 0.7 ms its spontaneous spike was still en route to the site of stimulation in the pyramidal tract, and thus collision/nullification of spontaneous and evoked spikes occurred. (Adapted with modifications from Stout and Beloozerova, 2012). …”
Section: Characteristics Of Neurons Included In This Reviewmentioning
confidence: 99%
“…Instead, each of the motor centers contains a variety of neurons that differ in the phases of their discharges during the stride, in the number of PEFs they produce per cycle, in the manner by which they respond to the accuracy demand imposed by the ladder, and other parameters. We did our best to describe these different cell types in our original research reports (Marlinski et al, 2012a,b; Stout and Beloozerova, 2012). In Figure 7 we show neurons with shoulder-related receptive fields that belong to the most populous group of cells: those that discharge a single PEF per cycle and respond to accuracy demand on stepping by increasing the magnitude of their stride-related modulation and by shortening the PEF.…”
Section: Examples Of Locomotion-related Activity Of Neurons Across Thmentioning
confidence: 99%
See 2 more Smart Citations